Local Determinants of Crime: Distinguishing between Resident and Non-resident Offenders - Thiess Büttner; Hannes Spengler (Technische Universität Darmstadt, Department of Law and Economics, 2003)
The paper revisits the local determinants of crime using a spatial model distinguishing between resident and non-resident offenders. Employing data for German municipalities, the model is estimated by means of a spatial GMM approach. Focusing on resident offenders legal earnings opportunities and the expected gain from offenses are found to be important determinants of crime. Also the socio-economic background in terms of unemployment, poverty, and inequality proves significant for both property and violent crime. Whereas local inequality only shows an effect on crime committed by resident offenders, crime committed by non-resident offenders is shown to be significantly related to the characteristics in adjacent municipalities such as unemployment and income.
Keywords: K42; R19; J61; J19; 330; Crime; Causes of Crime; Cross-Sectional Study; Spatial Econometrics; Crime Spillovers; Neighborhood Effects; Instrumental Variables; Straftäter; Kriminalitätsökonomik; Räumliche Interaktion; Wohnstandort; Schätzung; Deutschland